2016
DOI: 10.1080/15685551.2016.1231035
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sulfonation degree on molecular weight, thermal stability, and proton conductivity of poly(arylene ether sulfone)s membrane

Abstract: Direct copolymerization of sulfonated and non-sulfonated difluorodiphenyl sulfones as dihalide monomers with hydroquinone and also 4,4′-(4,4′-sulfonylbis-(1,4-phenylene)bis(oxy)) diphenol as diols led to preparation of two series of poly(arylene ether sulfone)s. Copolymers with different degrees of sulfonation (40, 50 and 60%) were synthesized in order to evaluate their potential for fuel cell application. 1H-NMR, FT-IR, and mass spectroscopy were used for characterization of prepared monomers and copolymers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 45 publications
2
25
0
Order By: Relevance
“…Nuclear Magnetic Resonance (NMR) study for estimation of the sulfonation content showed that the degree of sulfonation in Poly(ether sulfone) based on 4,4 0 -(4,4 0 -Sulfonylbis-(1,4phenylene)bis(oxy)) diphenol (PES-SPHD) series was lower than similar structures in Poly(ether sulfone) based on Hydroquinone (PES-HQ) series, resulting in lower IEC values in PES-SPHD chains. [49] Water uptake and dimensional stability showed a similar trend (Table 1); it means that both properties in two groups of copolymers increased as the degree of sulfonation increased, implying that more phase separation happened. Another assumption was that in SPHD-based copolymers, more free volume formed in copolymer structure and sulfonic acid groups become more accessible because of the presence of larger hydrophobic-hydrophilic segments.…”
Section: Resultsmentioning
confidence: 68%
See 4 more Smart Citations
“…Nuclear Magnetic Resonance (NMR) study for estimation of the sulfonation content showed that the degree of sulfonation in Poly(ether sulfone) based on 4,4 0 -(4,4 0 -Sulfonylbis-(1,4phenylene)bis(oxy)) diphenol (PES-SPHD) series was lower than similar structures in Poly(ether sulfone) based on Hydroquinone (PES-HQ) series, resulting in lower IEC values in PES-SPHD chains. [49] Water uptake and dimensional stability showed a similar trend (Table 1); it means that both properties in two groups of copolymers increased as the degree of sulfonation increased, implying that more phase separation happened. Another assumption was that in SPHD-based copolymers, more free volume formed in copolymer structure and sulfonic acid groups become more accessible because of the presence of larger hydrophobic-hydrophilic segments.…”
Section: Resultsmentioning
confidence: 68%
“…The two protons next to the sulfonate group on SDFS monomer were considered as reference peaks for evaluation as they were well separated from the other aromatic protons of all the copolymers. After complete characterization of monomers and polymers, and film preparation, mechanical and morphological properties of the prepared membranes were studied for application in fuel cell …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations